Organization and Implementation of Online Cytology Quality Assurance Program – Georgian Experience - Kldiashvili, Ekaterina; Romānovs, Andrejs; Shakulashvili, Nikoloz; Burduli, Archil; Ghortlishvili, Gocha; Agladze, Dodo (Electrical, Control and Communication Engineering, 2017)
Medical information system (MIS) is at the heart of information technology (IT) implementation policies in healthcare systems around the world. Different architecture and application models of MIS are developed. Despite of obvious advantages and benefits, application of MIS in everyday practice is slow. On the background of analysis of the existing models of MIS in Georgia has been created a multi-user web-based approach. This article will present the architecture of the system and its application for cytology quality assurance programs. Five hundred Georgian language electronic medical records from the cervical screening activity illustrated by images were selected for quality assurance program. The primary goal of the MIS is patient management. However, the system can be used for quality assurance programs. The ideal of healthcare in the information age must be to create a situation where healthcare professionals spend more time creating knowledge from medical information and less time managing medical information. The application of easily available and adaptable technology and improvement of the infrastructure conditions is the basis for eHealth applications. The MIS is perspective and actual technology solution. It can be used for cytology quality assurance programs.